Advances in polyurethane biomaterials - Cooper, Stuart L. 1941-; Guan, Jianjun (Woodhead Publishing, 2016)
Advances in Polyurethane Biomaterials brings together a thorough review of advances in the properties and applications of polyurethanes for biomedical applications. The first set of chapters in the book provides an important overview of the fundamentals of this material with chapters on properties and processing methods for polyurethane. Further sections cover significant uses such as their tissue engineering and vascular and drug delivery applications Written by an international team of leading authors, the book is a comprehensive and essential reference on this important biomaterial
Includes index
Keywords: TECHNOLOGY & ENGINEERING / Chemical & Biochemical; Biomedical materials; Polyurethanes